2014
DOI: 10.1016/j.molonc.2014.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐6 drives melanoma cell motility through p38α‐MAPK‐dependent up‐regulation of WNT5A expression

Abstract: Extensive research has demonstrated a tumor‐promoting role of increased WNT5A expression in malignant melanoma. However, very little light has been shed upon how WNT5A expression is up‐regulated in melanoma. A potential regulator of WNT5A expression is the pro‐inflammatory cytokine Interleukin (IL)‐6, which shares the ability of WNT5A to increase melanoma cell invasion. Here, we investigate whether IL‐6 can promote melanoma cell motility through an increased expression of WNT5A. We clearly demonstrate that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 48 publications
(80 reference statements)
3
64
0
Order By: Relevance
“…The algorithm phenotypically stratifies publicly available microarray data sets to classify individual melanoma cell lines as either proliferative or invasive [22]. As previously demonstrated [12], extracted data revealed that significantly increased mRNA expression of WNT5A (Figure 1A) is associated with an invasive phenotype signature of melanoma cells. Interestingly, the same association was discovered for the mRNA expression of IL-6 (Figure 1B).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The algorithm phenotypically stratifies publicly available microarray data sets to classify individual melanoma cell lines as either proliferative or invasive [22]. As previously demonstrated [12], extracted data revealed that significantly increased mRNA expression of WNT5A (Figure 1A) is associated with an invasive phenotype signature of melanoma cells. Interestingly, the same association was discovered for the mRNA expression of IL-6 (Figure 1B).…”
Section: Resultsmentioning
confidence: 97%
“…Similar to WNT5A, the pro-inflammatory cytokine IL-6 promotes melanoma cell invasion, and its increased expression is correlated with reduced overall patient survival [710]. Two recent studies have demonstrated a link between IL-6 secretion and WNT5A expression in melanoma cells [11, 12], suggesting that the combined therapeutic interference with this link might be beneficial for preventing disease progression and metastatic spread.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A regularly calibrated pH meter (FE20-FiveEasy, Mettler Toledo, Switzerland) was used to measure the solution pH. The living E. coli cells were counted using a Countess TM automatic cell counter (Invitrogen, USA) [34,35].…”
Section: Methodsmentioning
confidence: 99%
“…(69) Different studies indicate that WNT5A is regulated by the pro-inflammatory cytokine interleukin-6 (IL-6) in a p38a-MAPK-dependent manner. (70) Melanoma cell migration can be inhibited by targeting the RNA-binding protein human antigen R (HuR), which interacts with WNT5A mRNA, whereby HuR regulates its protein expression. (71) Moreover, WNT5A expression and secretion in melanoma is induced by the inhibition of the RNA helicase Mov10.…”
Section: Melanomamentioning
confidence: 99%